Draft Annual Plan 1986-87 Volume III General Areas Government of Assam - Planning Commission (Planning Commission, 1986)
The project was sanctioned by Planning Commission in 1979-80 at an estimated cost of Rs. 3636 lakhs. The original schedule for Commissioning of the project was by the end of 6th Five Year Plan. The project is being financed under OECF loan (Yen Credit) from Japan. The commissioning of the project has been delayed mainly due to slow progress in the dam .The contractor selected for the dam failed to procure the machineries and also decide on consultants for the work in time.
Government of Assam, Planning and Development Department